Chiral one‐ and two‐dimensional silver(I)–biotin coordination polymers. (5th February 2013) - Altaf, Muhammad; Stoeckli‐Evans, Helen
<x xml:space="preserve">Abstract</x> Reaction of biotin C10H16N2O3S, HL; systematic name: 5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoic acid with silver acetate and a few drops of aqueous ammonia leads to the deprotonation of the carboxylic acid group and the formation of a neutral chiral two‐dimensional polymer network, poly[[μ3‐5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoatosilver(I)] trihydrate], [Ag(C10H15N2O3S)]·3H2On or [Ag(L)]·3H2On, (I). Here, the AgI cations are pentacoordinate, coordinated by four biotin anions via two S atoms and a ureido O atom, and by two carboxylate O atoms of the same molecule. The reaction of biotin with silver salts of potentially coordinating anions, viz. nitrate and perchlorate, leads to the formation of the chiral one‐dimensional coordination polymers catena‐poly[[bis[nitratosilver(I)]‐bisμ3‐5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoato] monohydrate], [Ag2(NO3)2(C10H16N2O3S)2]·H2On or [Ag2(NO3)2(HL)2]·H2On, (II), and catena‐poly[bis[perchloratosilver(I)]‐bisμ3‐5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoato], [Ag2(ClO4)2(C10H16N2O3S)2]n or [Ag2(ClO4)2(HL)2]n, (III), respectively. In (II), the AgI cations are again pentacoordinated by three biotin molecules via two S atoms and a ureido O atom, and by two O atoms of a nitrate anion. In (I), (II) and (III), the AgI cations are bridged by an S atom and are coordinated by the ureido O atom and the O atoms of the anions. The reaction of biotin with silver salts of noncoordinating anions, viz. hexafluoridophosphate (PF6−) and hexafluoridoantimonate (SbF6−), gave the chiral double‐stranded helical structures catena‐poly[[silver(I)‐bisμ2‐5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoato] hexafluoridophosphate], [Ag(C10H16N2O3S)2](PF6)n or [Ag(HL)2](PF6)n, (IV), and catena‐poly[[[5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoatosilver(I)]‐μ2‐5‐[(3aS, 4S, 6aR)‐2‐oxohexahydro‐1H‐thieno[3, 4‐d]imidazol‐4‐yl]pentanoato] hexafluoridoantimonate], [Ag(C10H16N2O3S)2](SbF6)n or [Ag(HL)2](SbF6)n, (V), respectively. In (IV), the AgI cations have a tetrahedral coordination environment, coordinated by four biotin molecules via two S atoms, and by two carboxy O atoms of two different molecules. In (V), however, the AgI cations have a trigonal coordination environment, coordinated by three biotin molecules via two S atoms and one carboxy O atom. In (IV) and (V), neither the ureido O atom nor the F atoms of the anion are involved in coordination. Hence, the coordination environment of the AgI cations varies from AgS2O trigonal to AgS2O2 tetrahedral to AgS2O3 square‐pyramidal. The conformation of the valeric acid side chain varies from extended to twisted and this, together with the various anions present, has an influence on the solid‐state structures of the resulting compounds. The various O—H...O and N—H...O hydrogen bonds present result in the formation of chiral two‐ and three‐dimensional networks, which are further stabilized by C—H...X (X = O, F, S) interactions, and by N—H...F interactions for (IV) and (V). Biotin itself has a twisted valeric acid side chain which is involved in an intramolecular C—H...S hydrogen bond. The tetrahydrothiophene ring has an envelope conformation with the S atom as the flap. It is displaced from the mean plane of the four C atoms (plane B) by 0.8789 (6) Å, towards the ureido ring (plane A). Planes A and B are inclined to one another by 58.89 (14)°. In the crystal, molecules are linked via O—H...O and N—H...O hydrogen bonds, enclosing R22(8) loops, forming zigzag chains propagating along [001]. These chains are linked via N—H...O hydrogen bonds, and C—H...S and C—H...O interactions forming a three‐dimensional network. The absolute configurations of biotin and complexes (I), (II), (IV) and (V) were confirmed crystallographically by resonant scattering.